(NdRAMATURGIQ (B/ s (N~ASTX (B9s - (NtOLSTOJ(B, (NaLEKSEJ nIKOLAEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1986)
(Nw DEWQTYJ TOM sOBRANIQ SO^INENIJ WO[LI PXESY a(B. (Nn(B. (NtOLSTOGO RAZNYH LET(B.s
rus
Keywords: (NpXESYs; (NdRAMAs